The f-Ratio Quantification Method for X-ray Microanalysis Applied to Mg–Al–Zn Alloys. (4th February 2019) - Teng, Chaoyi; Demers, Hendrix; Chu, Xin; Gauvin, Raynald
Abstract: The f -ratio quantitative X-ray microanalysis method has been recently developed for binary systems based on a scanning electron microscope/energy dispersive spectroscopy (SEM/EDS) system. This method incorporates traditional EDS experiments and Monte Carlo simulations, and calibration factors are calculated with standard samples to evaluate the differences between them. In this work, the f -ratio method was extended to Mg–Al–Zn multi-element systems using a cold field emission SEM and a tungsten emission SEM. Results show that the stability of the beam current does not influence the f -ratio quantification accuracy. Thus, the f -ratio method is suitable for quantitative X-ray mapping with a long-time acquisition or even an unstable beam current. Comparing with other quantitative techniques including the routine standardless analysis and the standard-based k -ratio method, the f -ratio method is a simple and accurate quantification method.